Training and Mentoring Of Siaga Teens As An Efforts To Prevent Bullying In Schools: Pelatihan dan Pendampingan Remaja Siaga Sebagai Upaya Pencegahan Tindakan Bullying di Sekolah - Roida Simanjuntak, Susi; Buanasari, Andi; MoreenToar, Juwita (Universitas Haji Sumatera Utara, 2025)
Bullying is the act of harming others both physically and psychologically in the form of verbal, social, and physical violence. Bullying among adolescents can lead to serious health issues, both physical and mental. To this day, cases of bullying among teenagers remain very high and even show an increase each year. This poses a serious problem that must be addressed immediately. The implementation method for this activity involved training for adolescents conducted in two different schools in Manado, carried out in person. Before and after the activity, team conducted pre-test and post-test measurements to assess students' knowledge during the training. Based on the results of the pre-test and post-test, the knowledge assessment in the two middle schools showed an increase based on the average scores of the participants. Therefore, we concluded that there was an increase in participants' knowledge about bullying and its health impacts after the training was conducted for the students.